Structure and transport properties of La0.5Sr0.5 (-) xCaxFeO3 (-) (delta) - Chesnokov, K. Yu.
Effects of calcium doping on the structure, dimensional stability, and mixed oxygen-ion and electron conductivity of perovskite-like La0.5Sr0.5 - xCaxFeO3 - delta(x = 0-0.3) were studied in light of potential membrane applications. The incorporation of relatively small Ca2+ cations into the lanthanum-strontium ferrite lattice decreases unit cell volume, oxygen nonstoichiometry variations and chemical contribution to the thermal expansion in air. These changes correlate with rising tendency to local oxygen-vacancy ordering and the formation of nano-sized domains with the brownmillerite and LaCa2Fe3O8-type lattices, as revealed by electron diffraction. The resultant vacancy trapping, changing domain structure and enlargement of the interfacial boundary area lead to non-linear relationships between the partial ion conductivity and cation composition, while the apparent activation energy for ion transport at temperatures below 900 degrees C remains almost constant, 0.6-0.7 eV. The n-type electron contribution to the total conductivity, measured in the oxygen pressure range 10(-20)-0.5 atm at 700-950 degrees C, is also essentially independent of the calcium concentration. (C) 2013 Elsevier B.V. All rights reserved.